Analisis Pengelompokkan Persediaan Jenis Bahan Baku Rotan dengan Menggunakan Metode ABC - Muhammad Sayuti (Universitas Teuku Umar, 2016)
PT Bumi Selawah kab.pidie is an industrial company that was founded under perhaps the industry kab.pidie engaged in furniture products are made from rattan. In a production system the company has not classifying products which require priority highest amount of raw material. This is evident from observations in 2014-2015. Where the supply of raw materials is different each year. In 2014 the company supplying raw rattan by 20 tons, which is used only 12 tons, in 2015 the company supplied 10 tons, which is used only 9 tons. The results showed that the total percentage of absorption of funds amounting to 99.6%, where the cumulative percent of items of goods, Rattan Semanow (24-29) 11.11%, Rattan Semanow (40) 22.22%, Rattan Semanow (35-39) 33.33%, Rattan Semanow (18-23) 44.44%, 55.55% Track Rattan, Rattan Fega 66.66%, Semanow (30-34) 77.77%, Semanow (15-17) 88, Rattan Semanow 88% and 99.99%. There are 4 items that belong to class A, which supplies high-end, inventories are valued are classified in class B, and supplies the low value belongs to the class C so that the company can determine how much cane is needed for each category of the classification of the raw materials of rattan these, and order can be made as needed.Keywords: Inventory, ABC method, Rattan